Environmental control of CO2 assimilation rates and stomatal conductance in five oak species growing under field conditions in Greece - Radoglou, K (Ann. For. Sci., 1996)
The present study compared CO2 assimilation rate and stomatal conductance of five oak species from the beginning of May through November 1993 under similar natural conditions. Gas exchange, leaf characteristics and water status were measured on 30-year-old Quercus ilex, Q macrolepis, Q pedunculiflora, Q pubescens and Q trojana growing in experimental plots in northern Greece. The seasonal pattern of assimilation rates was similar for all study species but differences occurred between the species. After initial leaf expansion, all species rapidly developed high photosynthetic rates. In addition, assimilation rates were high in all species in May and November after rain events. No significant differences in stomatal conductance were observed among species during the growing season. The relationships between assimilation rate and stomatal conductance displayed variation in the slopes among species and months.
Keywords: assimilation rate; Drought; Quercus sp; Seasonality; Stomatal conductance

Use of pressure volume curves in water relation analysis on woody shoots: influence of rehydration and comparison of four European oak species - Dreyer, E.; Bousquet, F.; Ducrey, M. (Ann. For. Sci., 1990)
Pressure volume analyses were undertaken on leafy shoots of 4 European oak species (Quercus robur, Q petraea, Q pubescens and Q ilex) in order to determine the relationship between leaf water potential, average osmotic potential and volume averaged turgor. Some technical limitations of pressure volume analysis, as shown by the influence of the resaturation method on computed turgor, were overcome by accounting for losses of intercellular water during the first stages of dehydration. Variations in leaf to stem ratio, which are very important between large leaved oaks and small leaved evergreens, surprisingly did not influence the relative symplasmic volume of our samples. Differences in mean osmotic potential at full turgor (&Pi0) were related to species, with higher values in drought adapted species, and to leaf age and growing conditions. Values of volumetric modulus of elasticity (ε o) did not significantly influence the relations between leaf water potential (Ψw) and turgor (P) in different species. This relationship was mostly related to &Pi0. Finally, tolerance to drought appeared to be related more to the ability to osmotically adjust in response to changes in environment rather than to the absolute values of &Pi0.
Keywords: pressure-volume curve; Quercus sp; turgor; water potential; water relations

Use of pressure volume curves in water relation analysis on woody shoots: influence of rehydration and comparison of four European oak species - Dreyer, E; Bousquet, F; Ducrey, M (Ann. For. Sci., 1990)
Pressure volume analyses were undertaken on leafy shoots of 4 European oak species (Quercus robur, Q petraea, Q pubescens and Q ilex) in order to determine the relationship between leaf water potential, average osmotic potential and volume averaged turgor. Some technical limitations of pressure volume analysis, as shown by the influence of the resaturation method on computed turgor, were overcome by accounting for losses of intercellular water during the first stages of dehydration. Variations in leaf to stem ratio, which are very important between large leaved oaks and small leaved evergreens, surprisingly did not influence the relative symplasmic volume of our samples. Differences in mean osmotic potential at full turgor (&Pi0) were related to species, with higher values in drought adapted species, and to leaf age and growing conditions. Values of volumetric modulus of elasticity (ε o) did not significantly influence the relations between leaf water potential (Ψw) and turgor (P) in different species. This relationship was mostly related to &Pi0. Finally, tolerance to drought appeared to be related more to the ability to osmotically adjust in response to changes in environment rather than to the absolute values of &Pi0.
Keywords: pressure-volume curve; Quercus sp; turgor; water potential; water relations